High-intensity physiological activation disrupts the neural signatures of conflict processing - Chiara Avancini; Luis F. Ciria; Clara Alameda; Ana F. Palenciano; Andrés Canales-Johnson; Tristan A. Bekinschtein; Daniel Sanabria (Communications Biology)
Abstract Physiological activation fluctuates throughout the day. Previous studies have shown that during periods of reduced activation, cognitive control remains resilient due to neural compensatory mechanisms. In this study, we investigate the effects of high physiological activation on both behavioural and neural markers of cognitive control. We hypothesize that while behavioural measures of cognitive control would remain intact during periods of high activation, there would be observable changes in neural correlates. In our electroencephalography study, we manipulate levels of physiological activation through physical exercise. Although we observe no significant impact on behavioural measures of cognitive conflict, both univariate and multivariate time-frequency markers prove unreliable under conditions of high activation. Moreover, we observe no modulation of whole-brain connectivity measures by physiological activation. We suggest that this dissociation between behavioural and neural measures indicates that the human cognitive control system remains resilient even at high activation, possibly due to underlying neural compensatory mechanisms.